East Asia in American Geostrategic Orientations (قضايا سياسية, 2025)
The 21st century brought significant shifts in American strategic orientations, as Asia, particularly its eastern region, emerged as the new focus of U.S. geostrategy. Previously, Europe had been the primary point of interest following World War II, after which the Middle East, with its complexities and major interactions, took center stage in American strategic concerns. The primary reason for this shift was the rise of a new competitor seeking regional expansion—China.